2005
DOI: 10.1002/neu.20182
|View full text |Cite
|
Sign up to set email alerts
|

Responses of cerebral GABA-containing CBM neuron to taste stimulation with seaweed extracts inAplysia kurodai

Abstract: Aplysia kurodai distributed along Japan feeds well on Ulva pertusa but rejects Gelidium amansii with distinctive patterned movements of the jaws and radula. On the ventral side of the cerebral M cluster, four cell bodies of higher order neurons that send axons to the buccal ganglia are distributed (CBM neurons). We have previously shown that the dopaminergic CBM1 modulates basic feeding circuits in the buccal ganglia for rejection by firing at higher frequency after application of the aversive taste of seaweed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The presence of GABAli fibers in each of the connectives joining the central ganglia suggests an involvement of GABAergic neurons in the coordination or specification of behavior in Biomphalaria . Two GABAergic cerebral‐buccal interneurons (CBIs), termed CBI‐12 and CBI‐3, were identified in Aplysia (Euopisthobranchia, Anaspidea) and shown to exert specific GABA‐mediated actions on the feeding CPG (Jing et al, ; Wu et al, ; see also Narusuye et al ). In Clione limacina (Euopisthobranchia, Pteropoda) a GABAergic CBI termed Cr‐BM coordinates three motor programs that implement an elaborate carnivorous motor program (Norekian & Malyshev, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of GABAli fibers in each of the connectives joining the central ganglia suggests an involvement of GABAergic neurons in the coordination or specification of behavior in Biomphalaria . Two GABAergic cerebral‐buccal interneurons (CBIs), termed CBI‐12 and CBI‐3, were identified in Aplysia (Euopisthobranchia, Anaspidea) and shown to exert specific GABA‐mediated actions on the feeding CPG (Jing et al, ; Wu et al, ; see also Narusuye et al ). In Clione limacina (Euopisthobranchia, Pteropoda) a GABAergic CBI termed Cr‐BM coordinates three motor programs that implement an elaborate carnivorous motor program (Norekian & Malyshev, ).…”
Section: Discussionmentioning
confidence: 99%
“…shown to exert specific GABA-mediated actions on the feeding CPG Wu et al, 2003; see also Narusuye et al 2005). In Clione limacina (Euopisthobranchia, Pteropoda) a GABAergic CBI termed Cr-BM coordinates three motor programs that implement an elaborate carnivorous motor program (Norekian & Malyshev, 2005).…”
Section: Buccal Ganglia Of Lymnaea Stagnalis and Helisoma Trivolvismentioning
confidence: 99%
“…The vast majority of the GABA‐ir fibers and axons in the buccal ganglia of Nudipleura are restricted to the buccal connectives, the commissures; the neuropil region of each hemiganglion; and there is very limited GABAergic innervation of the periphery. In nudibranchs, a maximum of two GABA‐ir neurons from Ce ɣL cluster of the cerebral ganglia have axons in the CBC (Gunaratne et al, ) and GABA‐ir cerebral–buccal neurons have been shown to play important roles in initiating and regulating feeding behavior in species such as Aplysia californica (Jing et al, ; Wu et al, ), Aplysia kurodai (Narusuye et al, ), and Clione limacina (Norekian and Malyshev, ). We observed two or more GABA‐ir fibers in the CBC of all the Nudipleura species, and one of the sources of these axons may be GABA‐ir buccal–cerebral neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The Aplysia GABA‐ir neurons in this region that project to the buccal ganglion via the CBC were identified as the cerebral buccal interneurons, CBI‐3 and CBI‐11, both of which are involved in feeding behavior (Jing et al, ; Wu et al, ). A homologous neuron to the GABA‐ir CBI‐3 neuron was also found in the related Aplysiid, Aplysia kurodai (Narusuye et al, ). Clione also contains an identified feeding neuron (Cr‐BM) that is GABA‐ir, located in the anterior lateral cerebral ganglion, and projected to the buccal ganglia via the CBC (Norekian and Malyshev, ).…”
Section: Discussionmentioning
confidence: 99%